A review of clearwing moths in the tribe Synanthedonini, with descriptions of six new species from Taiwan (Lepidoptera: Sesiidae) - Liang, Jia-Yuan; Hsu, Yu-Feng (Zootaxa, 2015)
The Synanthedonini fauna of Taiwan is reviewed, and a checklist of 9 species for this region is provided. Six new species are described: Paranthrenella dortmundi Liang & Hsu sp. nov., Paranthrenella weiyui Liang & Hsu sp. nov., Ichneumenoptera gryphus Liang & Hsu sp. nov., Kantipuria glansvorax Liang & Hsu sp. nov., Synanthedon ceraunus Liang & Hsu sp. nov., and Synanthedon phoenix Liang & Hsu sp. nov. New records of relationships between host plants and the immatures of Synanthedonini in Taiwan are also provided, with three species feeding on callus tissue of stems of Fagaceae, two on Lauraceae, and one on Rosaceae. One species is an obligatory borer into acorns of Fagaceae, and such kind of feeding strategy is rare among clearwing moths.